Urgensi Pencatatan Perkawinan Pada Masyarakat Muslim Di Kelurahan Kampung Nangka, Binjai Utara - Tengku Keizerina Devi Azwar; Utary Maharany Barus; Yefrizawati Yefrizawati (Universitas Medan Area, 2022)
This study aims to find out the essence of the importance of recording marriages in Muslim communities in Kampung Nangka Village, North Binjai. As mandated by Article 1 of Law no. 1 of 1974 concerning Marriage that marriage is an inner and outer bond of a man and a woman as husband and wife with the aim of forming a happy and eternal family based on God Almighty. One of the most important things to do is register the marriage. The fact is that in the community, especially in remote areas, marriage registration in official state documents is rarely done. This research is a normative legal research with analytical descriptive nature by using a literature approach and a field approach. Analysis of the data obtained in this study was carried out qualitatively. The results of the study indicate that the problem of the lack of marriage registration is caused by several factors, such as the lack of knowledge of some people to the laws and regulations regarding marriage, both from the Islamic legal aspect and the positive legal aspect, the existence of some people who still carry out unregistered marriages for various reasons. This can prevent problems that can harm one party if the marriage is not recorded. Many people do not understand the importance of registering marriages that have been carried out and the consequences because marriages are not registered